FORMULATION STRATEGY OF MERCHANT BUSINESS GROUP DIVISION OF PT. BANK CIMB NIAGA, TBK - Rangkuti , Zulkifli; Faras Zulina Ayunani (IJRDO - Journal of Business Management, 2020)
Now a days, the transaction in Indonesia have a good growth and almost cashless. People like to using card for doing transaction in merchant or store. Along with that, banking industry see the opportunities in that situation, so they also provide facilities to process the transaction. PT. Bank CIMB Niaga, Tbk as one of acquiring bank in Indonesia should have a good strategy to dealing with the competition among acquiring bank. This study aims to analyze opportunities and threats faced by the Merchant Business Division of PT. Bank CIMB Niaga, Tbk, also posessed stregths and weaknessess of merchant business of PT. Bank CIMB Niaga, Tbk in developing the merchant product in acquiring business competition to improve the ranking of merchant business PT. Bank CIMB Niaga, Tbk in the merchant acquiring industry. Then to formulate and identify which strategy that should be applied in merchant business division of PT. Bank CIMB Niaga, Tbk